An investigation into Shaker-like potassium channel Kv1.6 and its role in the somatosensory nervous system - Peck, L (2019)
Pain is a fascinatingly malleable sensory percept, evoking a unique experience for each individual. Most people who have experienced pain have an inherent understanding of its unpleasantness, and under most conditions this negative affect drives short- and long-term behavioural changes, which serve to protect organisms from potential further harm relating to the offending stimulus. Most commonly, pain is short-lasting, associated with observable physical damage to the body, and reversible. Chronic pain is long-lasting, persisting even after recovery of tissue damage, which can instil societal stigma towards sufferers. ‘Neuropathic’ pain, associated with prior lesion of the nervous system, is typified by spontaneous pain sensation and pain evoked by non-noxious stimuli – a debilitating symptomatic experience and major global health burden.